2017
DOI: 10.1155/2017/3749627
|View full text |Cite
|
Sign up to set email alerts
|

The Nutritional Composition of Maca in Hypocotyls (Lepidium meyeniiWalp.) Cultivated in Different Regions of China

Abstract: Maca (Lepidium meyeniiWalp.) was introduced to China in the recent two decades. Proximate compositions and secondary metabolites in dried maca tuber powders of different cultivation areas and colour types were analyzed and compared in order to provide the scientific guideline for its application. Cultivation region significantly affects the compositions of maca. The protein content of maca ranged from 9.31% to 21.02% by dry basis of maca powders and Xiaopingba-Y, Yulong-Y, and Pamirs-Y have the higher protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 20 publications
0
37
4
1
Order By: Relevance
“…Other studies have shown that the cultivation area can significantly affect the nutritional and metabolite content of maca. For example, yellow maca samples grown in China had a higher mineral and protein content than yellow maca grown in Peru (Zhang et al, 2015, Chen et al, 2017. Additionally, most scientific studies investigated the properties of Peruvian maca but not Chinese maca (see appendix 2).…”
Section: Cultivation Practices and Area Of Cultivationmentioning
confidence: 99%
“…Other studies have shown that the cultivation area can significantly affect the nutritional and metabolite content of maca. For example, yellow maca samples grown in China had a higher mineral and protein content than yellow maca grown in Peru (Zhang et al, 2015, Chen et al, 2017. Additionally, most scientific studies investigated the properties of Peruvian maca but not Chinese maca (see appendix 2).…”
Section: Cultivation Practices and Area Of Cultivationmentioning
confidence: 99%
“…A recent study performed on maca cultivated in four different high-altitude areas of China and one from Peru showed that the content of benzyl glucosinolate (one of several glucosinolates) and N-benzyl hexadecanamide (one of several macamides) for all the plants of Chinese origin was significantly higher than from Junín, Peru. However, the total alkaloid level of the Peruvian sample was significantly higher than samples from three of the four Chinese locations [27].…”
Section: Introductionmentioning
confidence: 60%
“…Clement et al [8] reported that there are differences in Gls between ecotypes and the lead color ecotype of maca has higher total Gls than that of yellow, pink and violent. Supporting to this, black maca has more benzyl glucosinolate than yellow and purple macas [18]. But, other researchers found out that various ecotypes have Gls in similar quantities and there is not an influence of ecotype on Gls content in maca [20].…”
Section: Antioxidants In Foods and Its Applicationsmentioning
confidence: 82%
“…Czechia, the most of the N-benzylhexadecanamide is in that of China, then Peru and Czehia respectively. Further, macamide was not detected in maca grown in greenhouse [18,27,28]. However the above-mentioned studies argue that ecotype has no effect on macamide, they were reported that violent color of hypocotyl has higher total macamide than yellow, pink and lead colors of them [8].…”
Section: Alkamidesmentioning
confidence: 94%
See 1 more Smart Citation